Unstable intertrochanteric fractures: How to prevent uncontrolled impaction and shortening of the femur - Bogosavljević Miodrag; Stokić Dragan; Friščić Žan; Ristić Branko M. (Vojnosanitetski Pregled)
Background/Aim. Unstable intertrochanteric (IT) fractures, especially fractures with a reverse or transverse fracture line, have tendencies to make significant impaction on shortening of the femoral neck and lower extremity. The biomechanical complexity of the fracture, the type and the position of the implant are known to influence postoperative outcome. The aim of this study was to compare characteristics of two versions of dynamic hip implants in controlling the dynamization of unstable IT fractures of the femur. Methods. In the prospective study that included 1,115 patients with fractures of the proximal femur, 61 patients had IT fractures with a reverse or transverse fracture line. All the patients were treated surgically with the same implant in two versions: Dynamic Hip Screw - DHS-MB-S implant with a rigid part of standard length (40 mm) and DHS-MB-I implant, with a rigid part of the implant individualized for each patient depending on the transverse diameter of the proximal femur. The patients were under gradual radiographic and clinical control. Six months postoperatively we measured the length of the extremity and the degree of the medialization of the distal part of the femur. Results. All the fractures healed six months after the operation. Medialization and shortening of the extremity were significantly less in the group with fractures fixed by the DHSMB- I implant, in which length of the rigid part of the implant was preoperatively measured individually for each patient. Conclusion. In order to achieve a desired functional result, the control of dynamisation in unstable IT fractures is significant in the fixation of these fractures of the femur. We presented possible methods to realize it by the contact of the rigid part of our implant with medial cortex of the proximal fragment of the femur.